ANALISA DAN PERANCANGAN APLIKASI MANAJEMEN KINERJA CV. MEDIA KREATIF ONLINE - Eka Oktaviani; Hendi Setiawan; Kevin Perdana (LPPM STMIK BANDUNG, 2019)
The performance management system is a systematic approach to evaluating the company's project and condition using financial and non-financial measurements that compare the company's performance with other companies. With indicators, an organization can be assessed how much success it has in achieving company goals. Therefore, it is necessary to improve the design of performance measurement tools. This study used visual studio code software and the methodology to develop this system was Iterative Incremental.